The association between chronic airflow obstruction and poverty in 12 sites of the multinational BOLD study. Issue 6 (1st June 2017) - Townend, John; Minelli, Cosetta; Mortimer, Kevin; Obaseki, Daniel O.; Al Ghobain, Mohammed; Cherkaski, Hamid; Denguezli, Myriam; Gunesekera, Kirthi; Hafizi, Hasan; Koul, Parvaiz A.; Loh, Li C.; Nejjari, Chakib; et al.
Poverty is strongly associated with mortality from COPD, but little is known of its relation to airflow obstruction. In a cross-sectional study of adults aged ≥40 years from 12 sites (N=9255), participating in the Burden of Obstructive Lung Disease (BOLD) study, poverty was evaluated using a wealth score (0–10) based on household assets. Obstruction, measured as forced expiratory volume in 1 s (FEV1 )/forced vital capacity (FVC) (%) after administration of 200 μg salbutamol, and prevalence of FEV1 /FVC<lower limit of normal were tested for association with poverty for each site, and the results were combined by meta-analysis. Mean wealth scores ranged from 4 in Blantyre (Malawi) and Kashmir (India) to 10 in Riyadh (Saudi Arabia), and the prevalence of obstruction, from 16% in Kashmir to 3% in Riyadh and Penang (Malaysia). Following adjustments for age and sex, FEV1 /FVC increased by 0.36% (absolute change) (95%CI: 0.22, 0.49; p<0.001) per unit increase in wealth score. Adjustments for other confounders reduced this effect to 0.23% (0.11, 0.34), but even this value remained highly significant (p<0.001). Results were consistent across sites (I 2 =1%; phet =0.44). Mean wealth scores explained 38% of the variation in mean FEV1 /FVC between sites (r 2 =0.385, p=0.031). Airflow obstruction is consistently associated with poverty at individual and community levels across several countries. Poverty is a strong predictor of chronic airflow obstruction independent of age, sex, smoking and tuberculosis http://ow.ly/T2Sz30bdUNC